River of the sun: Stories of the storied Gila - Calvin, Ross frey50 (Albuquerque, NM The University of New Mexico Press, 1946)
The Gila river was viewed by Europeans before they saw the Hudson or the Delaware. Eighty years would pass before anyone stood on Plymouth rock. This area of land is an old land, having seen the coming of the Spaniards, the boom days of mining camps, the battles of Apache versus the calvary and settlers, and the beginning of the livestock industry, stamping out cattle rustling and establishing cattle ranches across the area.
Autographed copy
Keywords: New Mexico - History -- 1540 - 1940 -- Arizona - New Mexico; Gila River